Functional responses of aquatic macroinvertebrates to flow regulation are shaped by natural flow intermittence in Mediterranean streams. (19th March 2019) - Belmar, Oscar; Bruno, Daniel; Guareschi, Simone; Mellado‐Díaz, Andrés; Millán, Andrés; Velasco, Josefa
Abstract: Running waters in Mediterranean regions are strongly regulated by dams, which produce significant alterations to natural flow regimes. Climate change will reduce discharge and increase flow intermittence in Mediterranean streams, which will lead to an intensified flow regulation to meet water demands. Very little is known about how the functional features of aquatic communities vary along combined anthropogenic flow alteration and natural intermittence gradients. As intermittent streams are subjected to natural stress (droughts and flash floods), the flow regime alteration effect may differ from that observed in perennial rivers. Consequently, studies that aim to determine the effects of flow regulation on the functioning of aquatic communities in a global change context are crucial. By applying linear mixed‐effect models and null models to the macroinvertebrate communities from 65 stream sites in the Segura River Basin (south‐east Spain), we assessed the separate effects of natural flow intermittence and flow regulation, as well as their interaction, on biological traits and functional diversity indices. Natural flow intermittence and flow regulation were mainly associated with loss of taxa with semivoltine or univoltine cycles and more sensitive aquatic stages (i.e. eggs), and with the replacement by taxa with multivoltine cycles and more resistant aquatic stages (i.e. adults). Flow regulation intensified the impact of natural flow intermittence on some biological traits, producing synergistic effects (i.e. decreasing interstitial taxa and tegument breathers and increasing taxa with aquatic adult stages). At the same time, antagonistic (life cycle) and opposing (shredders) interaction effects were also observed. Functional diversity, functional dispersion, and functional redundancy underwent a non‐random decrease as the flow regime alteration increased, and a significant antagonistic interaction was also found between both stressors for functional redundancy. In general, flow regulation effects were stronger in perennial than in intermittent streams because natural intermittence imposes a previous eco‐evolutionary pressure on aquatic biota by selecting those resistant or recovery traits that confer resilience to anthropogenic flow regime alterations. Thus, the natural flow regime influences the functional sensibility of communities to anthropogenic flow alteration.